Rapamycin/IL-2 Combination Therapy in Patients With Type 1 Diabetes Augments Tregs yet Transiently Impairs β-Cell Function - Long, S. Alice; Rieck, Mary; Sanda, Srinath; Bollyky, Jennifer B.; Samuels, Peter L.; Goland, Robin; Ahmann, Andrew; Rabinovitch, Alex; Aggarwal, Sudeepta; Phippard, Deborah; Turka, Laurence A.; Ehlers, Mario R.; et al. (Diabetes (New York, N.Y.), 2012)
Rapamycin/interleukin-2 (IL-2) combination treatment of NOD mice effectively treats autoimmune diabetes. We performed a phase 1 clinical trial to test the safety and immunologic effects of rapamycin/IL-2 combination therapy in type 1 diabetic (T1D) patients. Nine T1D subjects were treated with 2-4 mg/day rapamycin orally for 3 months and 4.5 × 10(6) IU IL-2 s.c. three times per week for 1 month. β-Cell function was monitored by measuring C-peptide. Immunologic changes were monitored using flow cytometry and serum analyses. Regulatory T cells (Tregs) increased within the first month of therapy, yet clinical and metabolic data demonstrated a transient worsening in all subjects. The increase in Tregs was transient, paralleling IL-2 treatment, whereas the response of Tregs to IL-2, as measured by STAT5 phosphorylation, increased and persisted after treatment. No differences were observed in effector T-cell subset frequencies, but an increase in natural killer cells and eosinophils occurred with IL-2 therapy. Rapamycin/IL-2 therapy, as given in this phase 1 study, resulted in transient β-cell dysfunction despite an increase in Tregs. Such results highlight the difficulties in translating therapies to the clinic and emphasize the importance of broadly interrogating the immune system to evaluate the effects of therapy.